1989
DOI: 10.1007/bf02441469
|View full text |Cite
|
Sign up to set email alerts
|

Method for the measurement of susceptibility to decubitus ulcer formation

Abstract: A method for measuring the susceptibility of a patient to develop decubitus ulcers is described and initially evaluated. It is based on an indirect, noninvasive measurement of the transient regional blood flow response after a test pressure load which simulates the external stimulus for pressure-sore formation. This method was developed to determine the individual risk of a patient and to study the subfactors which contribute to the susceptibility. This would also offer the possibility of evaluating the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 6 publications
1
10
1
Order By: Relevance
“…Contrasting results were reported by Meijer et al (1989), who found a drop in temperature response during pressure application for all participants in their study. They used transient skin temperature response as a measure of blood flow response at greater depths in the tissue.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…Contrasting results were reported by Meijer et al (1989), who found a drop in temperature response during pressure application for all participants in their study. They used transient skin temperature response as a measure of blood flow response at greater depths in the tissue.…”
Section: Resultscontrasting
confidence: 99%
“…Skin temperature under pressure in subjects at risk and subjects not at risk . Skin temperature reaction during a period of pressure was studied by Knox, Anderson, and Anderson (1994); Meijer et al (1989); and Schubert and Heraud (1994). Schubert and Heraud found that subjects not at risk had a more pronounced increase in skin temperature than did subjects at risk.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considerable experience is required before either method can be used reliably. A major limitation is that very close control of the ambient temperature is needed [60] to obtain sufficient reproducibility.…”
Section: Skin Temperature and Humiditymentioning
confidence: 99%